2020
DOI: 10.1016/j.heliyon.2020.e03811
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment of saline extract from Pilosocereus gounellei (Cactaceae) and its chemopreventive effect against cyclophosphamide-induced DNA damage

Abstract: Pilosocereus gounellei (Cactaceae) is used to treat wounds and inflammation. In this study, we evaluated whether the saline extract from its stem would have genotoxic or anti-genotoxic effects. In the genotoxicity evaluation, mice received the extract (500, 1,000, or 2,000 mg/kg) orally while negative and positive controls were treated with saline solution (0.9% NaCl) per os and cyclophosphamide (CPA, 80 mg/kg i.p.), respectively. In the antigenotoxicity assay, using other animals, treatments were carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The number of chromosomal abnormalities in the zinc chloride-supported group were less than CP and comparable to the control group [figures 1 to 7]. Data in table [2] demonstrated that, the numbers and types of chromosomal abnormalities in bone marrow cells of rats of the CP-treated group had several chromosomal abnormalities such as ring chromosomes, deletion, fragmentation and polyploidy. When compared to the control group, the mean frequency of overall chromosomal abnormalities was considerably higher following CP therapy [0.34±0.40 versus 9.67±1.85].The pretreatment with ZnCl with CP showed significant reduction of chromosomal abnormalities that induced by CP [1.97 ±0.75].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The number of chromosomal abnormalities in the zinc chloride-supported group were less than CP and comparable to the control group [figures 1 to 7]. Data in table [2] demonstrated that, the numbers and types of chromosomal abnormalities in bone marrow cells of rats of the CP-treated group had several chromosomal abnormalities such as ring chromosomes, deletion, fragmentation and polyploidy. When compared to the control group, the mean frequency of overall chromosomal abnormalities was considerably higher following CP therapy [0.34±0.40 versus 9.67±1.85].The pretreatment with ZnCl with CP showed significant reduction of chromosomal abnormalities that induced by CP [1.97 ±0.75].…”
Section: Resultsmentioning
confidence: 94%
“…Cyclophosphamide [CP] has anticancer effects and harmful to normal cells, this bad effects may due to the imbalance of antioxidant system resulting in the accumulation of free radicals, Free radicals can cause DNA fragments, chromosomal aberrations [1] . Several studies demonstrated chromosomal aberrations caused by anticancer drugs in bone marrow cells [2,3] . So, it was necessary to use antioxidant materials to decrease the harmful impacts of CP and other anticancer drugs on normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…When AMS35BB is associated with CYC , there is a tendency to potentiate the genotoxic effects of the chemotherapeutic drug. , This can be confirmed by the frequency of cell death in the liver and kidneys. Although the potentiation of micronuclei did not appear significant, the extent of damage increased significantly.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, the saline extract from the stem of P. gounellei did not present significant toxic effects over 28 consecutive days and demonstrated antipyretic activity, together with hypoglycemic and hypolipidemic effects (Oliveira et al 2019). Still, when administered orally at the tested doses, the extract is genotoxically safe, when used with caution in doses above 1.000 mg/kg, and has a protective effect against CPA-induced DNA damage (Oliveira et al 2020).…”
Section: Biological Propertiesmentioning
confidence: 89%